ORTHOPEDIC TREATMENT OF PATIENTS WITH EDENTULOUS JAWS WITH COMPLETE REMOVABLE PLASTIC DENTURES USING ADHESIVE MATERIAL - O.V. Movchan (Український стоматологічний альманах)
The article reflects that one of the topical problems of orthopedic dentistry is an increase in the functional efficiency of removable dentures and prevention of atrophic changes in the supporting tissues of the prosthetic area by improving the methods of manufacturing prostheses. The solution to this problem is directly dependent on the specific clinical conditions. Under the above clinical conditions of the prosthetic area, the basis of the prosthesis should be differentiated, that is, the corresponding layer of adhesive material must restore the damping properties of the thin mucosal layer with low compliance, the prerequisite being the unloading of zones predisposed to atrophic processes and the load of sites resistant to atrophy.